The Impact of Renewable Energy on GDP - Abdullah; Javed, Aiman; Ashraf, Junaid; Khan, Tasir (International Journal of Management and Sustainability, 2020)
Besides traditional production factors, such as labor and capital, one of the inputs used in the production process is energy. Although the use of fossil fuels is more common in many production processes renewable energy sources are increasingly important in ensuring sustainable development. In many countries in the world, the share of renewable energy is the total energy consumption is very high, including in European Union (EU) countries. The purpose of this study is the investigate the output elasticity coefficients of capital and renewable energy in 12 EU countries by using the Cobb–Douglas production function approach. In this study, the Gross domestic Product these countries from 2000 to 2017, was examined using a generalized method of moments estimation, which used labor, capital, and renewable energy data. As a result of the study, the output elasticity coefficient in the Cobb–Douglas production function was found to be 1.147. This indicates that a 1% increase in labor, capital, and renewable energy increased GDP by 0.598%, 0.446%, and 0.093%, respectively. Among the findings, the relationship between GDP and explanatory variables is statistically significant and economically significant. It is understood that there is a positive relationship between the variables.